Related factors and prognostic significance of predialysis blood pressure variability - LV Yu-feng; DONG Hai-xia (Linchuang shenzangbing zazhi)
Objective To study the clinical variables that may plausibly influence predialysis systolic blood pressure variability(SBPV),and to investigate the correlations of predialysis SBPV with all-cause mortality in patients receiving prevalent maintenance hemodialysis(MHD).Methods A total of 50 patients were enrolled in the study.All the blood pressure values before each dialysis were recorded between March and May in 2011.The mean systolic pressure(SBP)was calculated,and SBPV was estimated with the coefficient of variability.During the three months,clinical data and related biochemical parameters were collected,and echocardiography was carried out to detect cardiac structure and function.Death events were recorded during the next five years.Results The predialysis SBPV was 8.5% ±2.1%.SBPV showed a positive correlation with the age,body mass index(BMI)and left atrial diameter(LAD)(P<0.05 for all).Meantime,SBPV showed a negative correlation with the serum creatinine(SCr),average DBP,parathyroid hormone(PTH),doses of calcium carbonate and activated vitamin D(P<0.05).Patients with diabetes mellitus(DM),coronary artery disease(CAD)or taking alfablocker had higher SBPV(P<0.05).SBPV was used as a variate for conducting the multiple linear regression analysis,after adjustment,the seven variables of age,DM,CAD,BMI,LAD,SCr and taking alfa-blocker maintained their associations with predialysis SBPV(P<0.05).The equation of R~2=0.630.During 5 years of follow-up,12 patients died(24.0%).The Kaplan-meier survival analysis showed that the predialysis SBPV elevation was associated with the mortality rate(P<0.01).Conclusions Advanced age,the history of DM and/or CAD,lower SCr,higher BMI and LAD,and taking alpha-blocker were the independent risk factors of increased predialysis SBPV.The predialysis SBPV increase is associated with all-cause mortality in patients given prevalent MHD.